Stable N‐Phosphanyl Acyclic Diaminocarbenes. Issue 20 (12th June 2014) - Marchenko, Anatoliy; Koidan, Georgyi; Hurieva, Anastasiya; Kurpiieva, Olena; Vlasenko, Yurii; Rozhenko, Alexander B.; Kostyuk, Aleksandr
Abstract: The deprotonation of N ‐di‐ tert ‐butylphosphanyl‐ N ‐aryl‐ N′ ‐diisopropylformamidinium salts led to a new type of stable acyclic N ‐phosphanyl‐diaminocarbene (PADC). Carbenes8a –8d were separated as single compounds. The molecular structure of8c was determined by X‐ray diffraction analysis. The PADC8 possess an optimal substitution pattern at the nitrogen atoms, and the N–Ccarbene –N bond angle is 120.7°. Structural changes near the carbenic carbon atom, such as substitution of phenyl with mesityl, phosphanyl with selenophosphoryl, or the diisopropylamino group with 2, 2, 6, 6‐tetramethylpiperidino, rendered them unstable. The PADCs underwent N, C‐phosphorus shifts to afford new C ‐phosphanylformamidines. Abstract : The deprotonation of P III N ‐substituted formamidinium salts afforded a new type of stable acyclic N ‐phosphanyl‐diaminocarbene. The carbenes possess an optimal substitution pattern, deviations from which make them unstable. They transform into C ‐phosphanylformamidines by a N, C‐phosphorus shift, which was studied by quantum chemistry calculations.